Features of circuitry of acousto-optic laser measuring systems for controlling three-coordinate (3D) movements of products and equipment elements. Part 1. - E. V. Leun (Омский научный вестник)
The article is devoted to the construction of acousto-optic (AO) laser measuring systems (LMS) for measuring product displacements in three coordinates (3D): with one longitudinal Δl z and two transverse Δl x , Δl y with high resolution and an increased measurement range for the latter two. The paper discusses the circuitry of the measuring circuit based on the phase-locked loop (PLL) system, which makes it possible to achieve the maximum resolution when the AO LMS operates in the start-stop mode, i.e. starting and ending with a stationary state at v=0. The paper considers the possibilities of using a prismatic optical scheme, which makes it possible to use a one-axis (1D) AO modulator to control two-coordinate (2D) displacements Δl x , Δl y of a laser beam, a multi-aperture AO modulator, a fiber photodetector and other units.